Design and Application of Intermittent Gear Mechanism with Intermittent Ratio Continuous Adjustment - Li Zhijie; Zhang Jin; Zhu Jian; Zeng Liwen (Jixie chuandong)
According to the requirement of automatic cutting tape,through studying the motion law of the intermittent mechanism,a novel incomplete gear intermittent mechanism is proposed,in which the intermittent ratio can be adjusted continuously. With detail structure design and parameter calculation,the problem of time interval between the tape clamped and cut of the intermittent mechanism in the automatic tape cutting device is solved by using the related program developed with software MATLAB. The continuous adjustment of the intermittent ratio is realized according to the tape width and length. The intermittent mechanism gives full play to the performance of equipment and the production efficiency is improved.